(untitled) (Літератури світу: поетика, ментальність і духовність, 2017)
In the article is researched the genre originality of the novel by Tetyana Belimova "Free World". It is specified that the peculiarity of author’s artistic thinking is realized through the modification of the genre: romance-chronicle, romance-family saga, romance-memories, romance-memory. An attempt is made to trace the metaphor of the "free world" as an image of the characters, both at the philosophical level.